GSK-3 Inhibitors: Preclinical and Clinical Focus on CNS - Eldar-Finkelman, Hagit; Martinez, Ana (Frontiers in Molecular Neuroscience, 2011)
Inhibiting glycogen synthase kinase-3 (GSK-3) activity via pharmacological intervention has become an important target for treating neurodegenerative and psychiatric disorders. The reported GSK-3 inhibitors are of diverse chemotypes and mechanisms of action that include compounds isolated from natural sources, cations, synthetic small-molecule ATP-competitive inhibitors, non-ATP-competitive inhibitors, and substrate-competitive inhibitors. Here we describe the variety of GSK-3 inhibitors with a specific emphasis on their biological activities in neurons and neurological disorders. We further highlight our current progress in the development of non-ATP-competitive inhibitors of GSK-3. The available data raises the hope that one or more of these drug design approaches will prove successful at stabilizing or even reversing the aberrant neuropathology and cognitive deficits of certain CNS disorders.